Malus rootstocks affect copper accumulation and tolerance in trees by regulating copper mobility, physiological responses, and gene expression patterns. (15th October 2021) - Wan, Huixue; Yang, Fengying; Zhuang, Xiaolei; Cao, Yanhong; He, Jiali; Li, Huifeng; Qin, Sijun; Lyu, Deguo
Abstract: We investigated the roles of rootstocks in Cu accumulation and tolerance in Malus plants by grafting 'Hanfu' (HF) scions onto M. baccata (Mb) and M. prunifolia (Mp) rootstocks, which have different Cu tolerances. The grafts were exposed to basal or excess Cu for 20 d. Excess Cu-treated HF/Mb had less biomass, and pronounced root architecture deformation and leaf ultrastructure damage than excess Cu-challenged HF/Mp. Root Cu concentrations and bio-concentration factor (BCF) were higher in HF/Mp than HF/Mb, whereas HF/Mb had higher stem and leaf Cu concentrations than HF/Mp. Excess Cu lowered root and aerial tissue BCF and translocation factor ( T f ) in all plants; however, T f was markedly higher in HF/Mb than in HF/Mp. The subcellular distribution of Cu in the roots and leaves indicated that excess Cu treatments increased Cu fixation in the root cell walls, which decreased Cu mobility. Compared to HF/Mb, HF/Mp sequestered more Cu in its root cell walls and less Cu in leaf plastids, nuclei, and mitochondria. Moreover, HF/Mp roots and leaves had higher concentrations of water-insoluble Cu compounds than HF/Mb, which reduced Cu mobility and toxicity. Fourier transform infrared spectroscopy analysis showed that the carboxyl, hydroxyl and acylamino groups of the cellulose, hemicellulose, pectin and proteins were the main Cu binding sites in the root cell walls. Excess Cu-induced superoxide anion and malondialdehyde were 28.6% and 5.1% lower, but soluble phenolics, ascorbate and glutathione were 10.5%, 41.9% and 17.7% higher in HF/Mp than HF/Mb leaves. Compared with HF/Mb, certain genes involved in Cu transport were downregulated, while other genes involved in detoxification were upregulated in HF/Mp roots and leaves. Our results show that Mp inhibited Cu translocation and mitigated Cu toxicity in Malus scions by regulating Cu mobility, antioxidant defense mechanisms, and transcription of key genes involved in Cu translocation and detoxification. Graphical abstract: Image 1 Highlights: Apple rootstocks can affect scion copper tolerance and accumulation. M. prunifolia rootstock reduced copper toxicity in scion better than M. baccata. M. prunifolia rootstock reduced copper accumulation and mobility. M. prunifolia rootstock activated antioxidant systems to quench Cu-induced ROS. M. prunifolia rootstock downregulated Cu transport genes.